Class Consciousness in the Novels of Jack London and George Gissing - Turan, Selin (2023)
This book examines the class consciousness in the novels of Jack London and George Gissing. The author conducted this study under the guidance of Prof. Dr. Cemile Günseli İşçi. The book explores how class consciousness is shaped and how characters deal with this awareness. The author expresses gratitude to everyone who contributed to the completion of this work. This study was carried out at Durham University with the support of a TÜBİTAK scholarship. The book provides an important contribution to the representation of class consciousness in literature.